EFFECT OF YOHIMBINE ON CLOMIPRAMINE-INDUCED SEXUAL DYSFUNCTION IN MALE RATS - SHESHADRI SHEKAR; MOHAMMED VAZIR; BINDHU KEMPANNA; SHIVA KUMAR MIRYALA; ASHOK SUBEDI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Object: The present investigation has been carried out to find out the effect of yohimbine on clomipramine-induced sexual dysfunction in male rats. Methods: The male rats were treated with clomipramine and yohimbine simultaneously for 60 days. During the treatment, all the male rats were challenged with the female rats which are in estrous phase and their sexual behavior was observed under dim red light. Half of the animals in each group and remaining on 60 day were sacrificed, blood was collected and serum separated. Testis was collected and preserved in 10% formalin for subsequent histopathological examination. th Results: The study reveals that yohimbine failed to antagonize the clomipramine-induced sexual dysfunction in male rats in all aspects, except the partial improvement in the sexual behavior. Conclusion: Yohimbine a well-known aphrodisiac failed to antagonize the clomipramine-induced sexual dysfunction in male rats. The decrease in testosterone levels, a decrease in spermatozoa count were continued even in the presence of yohimbine except improvement in the sexual behavior parameters. Hence, yohimbine could not be a safe antidote against clomipramine-induced sexual dysfunction in male rats. Keywords: Yohimbine, Clomipramine, Testosterone, Male rat sexual competence, Testicular damage.